2022
DOI: 10.3389/fonc.2022.1010074
|View full text |Cite
|
Sign up to set email alerts
|

A stratification system of ferroptosis and iron-metabolism related LncRNAs guides the prediction of the survival of patients with esophageal squamous cell carcinoma

Abstract: Ferroptosis and iron-metabolism have been widely reported to play an important role in cancer. Long non-coding RNAs (lncRNAs) are increasingly recognized as the crucial mediators in the regulation of ferroptosis and iron metabolism. A systematic understanding of ferroptosis and iron-metabolism related lncRNAs (FIRLs) in esophageal squamous cell carcinoma (ESCC) is essential for prognosis prediction. Herein, Pearson's correlation analysis was carried out between ferroptosis and iron-metabolism-related genes (FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This dataset was screened for 330 DEGs. And we identified phosphoGlycerol dehydrogenase(PHFDH), [ 26 ] C‐C motif chemokine receptor 10(CCR10), [ 27 ] transmembrane protein 92(TMEM92), [ 28 ] aldolase,fructose‐bisphosphate C Gene(ALDOC), [ 29 ] and X‐inactive specific transcipt(XIST) [ 30 ] as being significantly upregulated in the PO group, all of which are associated with promoting ferroptosis (Supplemental material S2). DEGs‐based KEGG enrichment analyses showed the enrichment of 20 pathways.…”
Section: Resultsmentioning
confidence: 99%
“…This dataset was screened for 330 DEGs. And we identified phosphoGlycerol dehydrogenase(PHFDH), [ 26 ] C‐C motif chemokine receptor 10(CCR10), [ 27 ] transmembrane protein 92(TMEM92), [ 28 ] aldolase,fructose‐bisphosphate C Gene(ALDOC), [ 29 ] and X‐inactive specific transcipt(XIST) [ 30 ] as being significantly upregulated in the PO group, all of which are associated with promoting ferroptosis (Supplemental material S2). DEGs‐based KEGG enrichment analyses showed the enrichment of 20 pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al [ 132 ] identified six genes associated with iron metabolism and iron death ( PRNP , SLC3A2 , SLC39A8 , SLC39A14 , ATP6V0A1 , and LCN2 ) in ESCC, and these genes may be associated with the infiltration of immune cells, tumor mutational load and ESCC prognosis. In addition, lncRNAs such as LINC01068, TMEM92-AS1 and AC243967.2 have been reported to be correlated with iron metabolism and iron death, and be closely related to the infiltration of immune cells in ESCC[ 133 ]. Moreover, Zhang et al [ 134 ] reported that mitochondrial energy metabolism is associated with the TIME and poor prognosis in ESCC patients, and identified several fatty acid metabolism-related genes that are predictors of EC prognosis[ 135 ].…”
Section: Tumor Cell-related Immunosuppressive Factorsmentioning
confidence: 99%